2018
DOI: 10.1111/sji.12648
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial extracellular vesicles modulate the macrophage phenotype: Potential implications in atherosclerosis

Abstract: Endothelial cells (ECs) and macrophages engage in tight and specific interactions that play critical roles in cardiovascular homeostasis and the pathogenesis of atherosclerosis. Extracellular vesicles (EVs) are circular membrane fragments released from the endosomal compartment as exosomes or shed from the surfaces of the membranes of most cell types. Increasing evidence indicates that EVs play a pivotal role in cell-to-cell communication. However, the contribution of EVs, as determine by oxidized low-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 45 publications
(106 reference statements)
1
83
0
Order By: Relevance
“…EVs also play a key role in the cross talk between ECs and macrophages that can either act in the direction of vascular homeostasis or promote atherosclerosis, depending on their composition. It was shown that EVs secreted by Kruppel-like factor 2-treated ECs show anti-inflammatory actions, while oxidized-LDLtreated ECs produce EVs with high levels of miR-155, directing macrophage differentiation toward pro-inflammatory M1 macrophages [54]. In M1, but not in M2 macrophages, the inflammasome is known to be activated [55] and the inflammasome signaling leads to the secretion of pro-inflammatory exosomes [56], further favoring atherosclerosis progression.…”
Section: Atherosclerosis and Vascular Calcification In Diabetes Mellitusmentioning
confidence: 99%
“…EVs also play a key role in the cross talk between ECs and macrophages that can either act in the direction of vascular homeostasis or promote atherosclerosis, depending on their composition. It was shown that EVs secreted by Kruppel-like factor 2-treated ECs show anti-inflammatory actions, while oxidized-LDLtreated ECs produce EVs with high levels of miR-155, directing macrophage differentiation toward pro-inflammatory M1 macrophages [54]. In M1, but not in M2 macrophages, the inflammasome is known to be activated [55] and the inflammasome signaling leads to the secretion of pro-inflammatory exosomes [56], further favoring atherosclerosis progression.…”
Section: Atherosclerosis and Vascular Calcification In Diabetes Mellitusmentioning
confidence: 99%
“…It is also reported that inflammatory stroke can induce extracellular vesicles macrophage activation [ 179 ], and these EVs can act as messengers of macrophages sensing atherogenic stimuli [ 180 ]. Furthermore, endothelial EVs can modulate the macrophage phenotype with potential implications to atherosclerosis in patients [ 181 ]. Conversely, macrophage-derived exosomes induce inflammatory factors in endothelial cells under hypertensive conditions [ 182 ], while macrophage-secreted exosomes can deliver an miRNA-21 inhibitor to regulate BGC-823 cell proliferation of gastric cancer cells [ 183 ].…”
Section: Exosomes and Macrophagesmentioning
confidence: 99%
“…It is well known that atherosclerosis, the hallmark sign of CVDs, is caused by dyslipidaemia and some studies have shown the role of EVs in the different stages of atherosclerosis [ 7 , 20 , 21 , 22 ]. Moreover, the number and phenotype of MVs have been associated with major cardiovascular risk factors such as smoking, diabetes mellitus, obesity, HT, dyslipidaemia and metabolic syndrome [ 19 ].…”
Section: Senescencementioning
confidence: 99%
“…Recently, MVs have emerged as new regulators of biological functions in atherothrombosis [ 19 ]. MVs produce inflammatory effects, cell proliferation, thrombosis and calcification in the vasculature and appear to in human atherosclerotic plaques [ 7 , 20 , 21 , 22 ]. However, the possible involvement of MVs, mainly derived from smooth muscle cells, in the calcification of atherosclerotic lesions was demonstrated a long time ago [ 149 ].…”
Section: Microvesicles In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation